Two-component epoxy glue for stone processing as well as preparation method and application of two-component epoxy glue

By optimizing the raw material composition and preparation method of two-component epoxy glue, the problem that existing epoxy resin glue is difficult to meet the stone processing requirements is solved, and the effects of high strength, low viscosity, high gloss and short early strength time are achieved, meeting the needs of stone processing and use.

CN119912889APending Publication Date: 2025-05-02袁媛
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411905127.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Existing epoxy resin glues are difficult to meet the use and processing requirements of stone at the same time, such as high viscosity, low gloss, poor yellowing resistance, or long curing time, which cannot meet the processing requirements of stone production lines.

Method used

A two-component epoxy glue is used, and its component A includes epoxy resin, modification diluent, additive and coupling agent, and component B includes curing agent, alicyclic amine modification curing agent and accelerator. By optimizing the dosage and preparation method of each raw material, the strength, low viscosity, gloss and time of early strength of the glue is improved.

Benefits of technology

Two-component epoxy adhesives with high strength, low viscosity, high gloss and short early strength time can meet the needs of stone processing and improve the processing efficiency and use value of stone.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005204204920000011
    Figure BDA0005204204920000011
  • Figure BDA0005204204920000112
    Figure BDA0005204204920000112
  • Figure BDA0005204204920000121
    Figure BDA0005204204920000121
Patent Text Reader

Abstract

The invention discloses two-component epoxy glue for stone processing and a preparation method and application thereof.The epoxy glue comprises a component A and a component B. The component A comprises, by weight, 72%-79% of epoxy resin, 11%-15% of modified diluent, 7%-10% of auxiliaries and 2%-5% of coupling agent. The component B comprises the following raw material components in percentage by weight: 37%-44% of a curing agent, 53%-61% of an alicyclic amine modified curing agent and 2%-3% of an accelerant, and the modified diluent is prepared from polypropylene glycol and epoxy chloropropane. The two-component epoxy glue has the advantages of high strength, low viscosity, high glossiness, short time for reaching early strength and the like, is a novel epoxy resin surface glue which is excellent in performance and can be widely applied to stone processing, can be widely applied to processing and production of stones (such as high-grade stones with ice cracks), and is high in use value and good in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a two-component epoxy adhesive for stone processing and a preparation method and application thereof. Background Art

[0002] During the stone processing, it is usually necessary to apply epoxy resin glue (also called epoxy glue) on the stone surface. On the one hand, epoxy resin glue can be used to repair cracks or gaps on the stone surface, and on the other hand, it can also increase the strength of the stone. At the same time, in order not to affect the processing efficiency of the stone production line, the processing requirements for the stone are: when the tensile shear strength is above 3MPa, the stone can be transported or moved, when the tensile shear strength is above 8MPa, it meets the stone processing requirements, and the Shore hardness reaches above 70D, which is convenient for stone grinding. In particular, by shortening the time for the stone surface to reach early strength, it is more conducive to meeting the stone processing requirements. However, the existing epoxy resin glue still cannot meet the use and processing requirements of stone at the same time. Specifically: (1) Epoxy resin glue with fillers can shorten the time required to reach early strength under the action of fillers, but such epoxy resin glue usually has defects such as high viscosity, low gloss, and poor yellowing resistance, which is not only not conducive to the smooth penetration of epoxy resin glue into the cracks or gaps on the surface of stone, but also reduces the original quality of the stone and cannot meet the use requirements of stone; (2) Epoxy resin glue without fillers usually has lower viscosity, high gloss, and good yellowing resistance, but its curing time is usually longer, or the time required to reach early strength is longer, which cannot meet the processing requirements of stone production lines. For example, the existing two-component epoxy resin glue without fillers has a very low viscosity, which can be as low as 26Pa.s / 25℃, and has high gloss and good yellowing resistance. However, when it is applied to the surface of stone, it usually has no strength within 4 hours and a strength of 2-3MPa after 12 hours, which cannot meet the processing requirements of stone production lines. Therefore, it is very necessary to develop a two-component epoxy adhesive with high strength, low viscosity, high gloss and short time to reach early strength, which is of great significance for improving the processing efficiency of stone and promoting the widespread use of stone. Summary of the invention

[0003] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a two-component epoxy adhesive for stone processing which has high strength, low viscosity, high gloss and a short time required to reach early strength, as well as a preparation method and application thereof.

[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0005] A two-component epoxy adhesive for stone processing, comprising component A and component B;

[0006] The component A comprises the following raw material components in terms of weight percentage:

[0007]

[0008] And the sum of the weight percentages of each raw material is 100%;

[0009] The B component comprises the following raw material components in terms of weight percentage:

[0010] Curing agent 37%~44%,

[0011] Alicyclic amine modified curing agent 53%~61%,

[0012] The accelerator is 2% to 3%, and the sum of the weight percentages of each raw material is 100%;

[0013] The modified diluent is prepared from polypropylene glycol and epichlorohydrin; the auxiliary agent is a modified product (mixture) of acrylic acid and pentaerythritol.

[0014] The above two-component epoxy adhesive is further improved, and the preparation method of the modified diluent includes the following steps: mixing polypropylene glycol and epichlorohydrin, and etherifying, cyclizing and refining under alkaline conditions to obtain the modified diluent.

[0015] The above two-component epoxy adhesive is further improved in that the molar ratio of the polypropylene glycol to epichlorohydrin is 2:1; the polypropylene glycol is polypropylene glycol 200 and / or polypropylene glycol 400.

[0016] The above two-component epoxy adhesive is further improved in that the epoxy equivalent of the modified diluent is 147.5 g / mol to 167.5 g / mol.

[0017] The above two-component epoxy adhesive is further improved in that the epoxy resin is a mixture of bisphenol A epoxy resin and bisphenol F epoxy resin.

[0018] The above two-component epoxy adhesive is further improved in that the weight ratio of the bisphenol A epoxy resin to the bisphenol F epoxy resin is 14-15:5-6.

[0019] The above two-component epoxy adhesive is further improved in that the epoxy equivalent of the epoxy resin is 185 g / mol to 188 g / mol.

[0020] The above two-component epoxy adhesive is further improved in that the molar ratio of acrylic acid to pentaerythritol in the auxiliary agent is 3:1; and the coupling agent is at least one of KH560 and KH570.

[0021] The above two-component epoxy adhesive is further improved, wherein the curing agent is at least one of triethylenetetramine, 1.3-BAC, and polyetheramine D230.

[0022] The above two-component epoxy adhesive is further improved in that the accelerator is a mixture of benzyl alcohol and salicylic acid; the weight ratio of the benzyl alcohol to salicylic acid is 72-81:19-28.

[0023] The above-mentioned two-component epoxy adhesive is further improved, and the alicyclic amine modified curing agent is prepared from a mixed solution of alicyclic amine curing agent and epoxy resin, comprising the following steps: adding alicyclic amine curing agent into a reactor, adjusting the temperature to 32°C to 36°C, dripping epoxy resin benzyl alcohol solution for 3h to 4h, and after the dripping is completed, adjusting the temperature to 38°C to 42°C and continuing the reaction for 2h to obtain the alicyclic amine modified curing agent.

[0024] The above-mentioned two-component epoxy adhesive is further improved, wherein the weight ratio of the alicyclic amine curing agent to the epoxy resin mixed liquid is 13-15:5-7; the alicyclic amine curing agent includes IPDA and PACM; the weight ratio of IPDA and PACM is 7-8:12-13; the epoxy resin mixed liquid includes epoxy resin E-51 and benzyl alcohol; the weight ratio of the epoxy resin E-51 and benzyl alcohol is 3-4:6-7.

[0025] The above two-component epoxy adhesive is further improved in that the weight ratio of component A to component B is 2.90-3.10:1.

[0026] As a general technical concept, the present invention also provides a method for preparing the above-mentioned two-component epoxy adhesive, comprising the following steps:

[0027] S1. Heat the epoxy resin to 60°C to 65°C, add a modified diluent, an auxiliary agent and a coupling agent in sequence, stir, and obtain component A; mix the curing agent, the alicyclic amine modified curing agent and the accelerator, adjust the temperature to 25°C to 35°C, stir, and obtain component B;

[0028] S2. Mix component A and component B to obtain a two-component epoxy adhesive.

[0029] The above preparation method is further improved in that during the preparation of component A, the stirring time is 75 min to 90 min.

[0030] The above preparation method is further improved in that during the preparation of the component B, the stirring time is 75 min to 90 min.

[0031] As a general technical concept, the present invention also provides an application of the above-mentioned two-component epoxy adhesive or the two-component epoxy adhesive prepared by the above-mentioned preparation method in stone processing.

[0032] Compared with the prior art, the advantages of the present invention are:

[0033] (1) In view of the defects of the existing two-component epoxy adhesive that it is difficult to meet the requirements of stone use and processing, the present invention provides a two-component epoxy adhesive for stone processing, including component A and component B. Component A includes the following raw material components by weight: epoxy resin 72% to 79%, modified diluent 11% to 15%, auxiliary agent 7% to 10%, coupling agent 2% to 5%, and component B includes the following raw material components by weight: curing agent 37% to 44%, alicyclic amine modified curing agent 53% to 61%, and accelerator 2% to 3%, and the modified diluent is prepared from polypropylene glycol and epichlorohydrin. In the present invention, the modified diluent used is prepared from polypropylene glycol and epichlorohydrin, has good toughness, impact resistance, and is convenient for improving glossiness. At the same time, the auxiliary agent used is a modified product of acrylic acid and pentaerythritol, which can react with an amine curing agent, is insensitive to temperature, and is an exothermic reaction, which can increase the temperature of the reaction system, so that other amine curing agents can react at a lower temperature, and can increase the strength more quickly. In particular, it has yellowing resistance and scratch resistance, and has the characteristics of low toxicity and low viscosity. In component B, the curing agent and the alicyclic amine modified curing agent mainly react with the epoxy resin, and have low-temperature reactivity, hydrophilic curing performance and yellowing resistance, and have low viscosity, which can reduce the mixed viscosity of the system. At the same time, the accelerator can accelerate the curing and promote the early strength, shortening the time required to achieve the early strength. On this basis, the present invention further optimizes the amount of each raw material in the A / B component, so that the two-component epoxy adhesive of the present invention exhibits more excellent performance, such as higher strength, lower viscosity, higher gloss, and shorter time required to reach early strength. It is a new type of epoxy resin surface adhesive with excellent performance and can be widely used in stone processing. It can be widely used in the processing and production of stone, and is particularly suitable for the repair and finishing of high-grade stone with ice cracks. It has high use value and good application prospects.

[0034] (2) In the present invention, the alicyclic amine modified curing agent is prepared from a mixed solution of an alicyclic amine curing agent and an epoxy resin, which is not only easy to control the viscosity and the usage ratio of the epoxy resin, but also can improve the glossiness. DETAILED DESCRIPTION

[0035] The present invention is further described below in conjunction with specific preferred embodiments, but the protection scope of the present invention is not limited thereby.

[0036] The raw materials and instruments used in the following examples are all commercially available; the equipment and preparation processes used are all conventional equipment and conventional processes unless otherwise specified.

[0037] Example 1

[0038] A two-component epoxy adhesive for stone processing, comprising component A and component B;

[0039] Component A includes the following raw material components in terms of weight percentage:

[0040] And the sum of the weight percentages of each raw material is 100%;

[0041] Component B includes the following raw material components in terms of weight percentage:

[0042] Curing agent 37%,

[0043] Alicyclic amine modified curing agent 61%,

[0044] The accelerator is 2%, and the sum of the weight percentages of each raw material is 100%.

[0045] In this embodiment, the modified diluent is prepared from polypropylene glycol and epichlorohydrin, which includes the following steps: mixing polypropylene glycol and epichlorohydrin, and performing etherification, cyclization and purification under alkaline conditions to obtain the modified diluent.

[0046] In this embodiment, the molar ratio of polypropylene glycol to epichlorohydrin is 2: 1. The polypropylene glycol is polypropylene glycol 200 or polypropylene glycol 400.

[0047] In this embodiment, the epoxy equivalent of the modified diluent is 152 g / mol.

[0048] In this embodiment, the epoxy resin is a mixture of bisphenol A epoxy resin and bisphenol F epoxy resin, and the weight ratio of bisphenol A epoxy resin to bisphenol F epoxy resin is 73:27. The epoxy equivalent of the epoxy resin is 185 g / mol.

[0049] In this embodiment, the auxiliary agent is a modified product (mixture) of acrylic acid and pentaerythritol, and the molar ratio of acrylic acid to pentaerythritol is 3:1.

[0050] In this embodiment, the coupling agent is KH560, or KH570, or a mixture thereof.

[0051] In this embodiment, the curing agent is triethylenetetramine, and may also be 1.3-BAC or polyetheramine D230.

[0052] In this embodiment, the accelerator is a mixture of benzyl alcohol and salicylic acid, wherein the weight ratio of benzyl alcohol to salicylic acid is 77:23.

[0053] In this embodiment, the alicyclic amine modified curing agent is prepared from an alicyclic amine curing agent and an epoxy resin mixed solution, comprising the following steps: adding the alicyclic amine curing agent into a reactor, adjusting the temperature to 32°C to 36°C, dripping the epoxy resin benzyl alcohol solution for 3h to 4h, and after the dripping is completed, adjusting the temperature to 38°C to 42°C and continuing the reaction for 2h to obtain the alicyclic amine modified curing agent, wherein the weight ratio of the alicyclic amine curing agent to the epoxy resin mixed solution is 73:27, the alicyclic amine curing agent includes IPDA and PACM, the weight ratio of IPDA to PACM is 37:63, and the epoxy resin mixed solution includes epoxy resin E-51 and benzyl alcohol, and the weight ratio of epoxy resin E-51 to benzyl alcohol is 7:13.

[0054] In this embodiment, the weight ratio of component A to component B is 3:1.

[0055] A method for preparing the two-component epoxy adhesive in the present embodiment comprises the following steps:

[0056] S1. Heat 72.0g of epoxy resin to 60℃~65℃, add 15.0g of modified diluent, 9.0g of auxiliary agent and 4.0g of coupling agent in sequence, stir for 80 minutes to obtain component A. Mix 37.0g of curing agent, 61.0g of alicyclic amine modified curing agent and 2.0g of accelerator, adjust the temperature to 25℃~35℃, stir for 80 minutes to obtain component B;

[0057] S2. Mix component A and component B to obtain a two-component epoxy adhesive, which can be used directly.

[0058] An application of the two-component epoxy adhesive in the present embodiment in stone processing is to apply the two-component epoxy adhesive to the surface of high-grade stone at 25°C.

[0059] After testing: the performance of the two-component epoxy adhesive in this embodiment is shown in Table 1. In addition, the two-component epoxy adhesive in this embodiment is applied to the surface of high-grade stone, cured at a temperature of 25°C, and its hardness and strength during the operation time are tested, and the results are shown in Table 1. The results show that after the two-component epoxy adhesive of the present invention is applied to the surface of the stone, the tensile shear strength reaches 4.2MPa after curing for 4h, that is, after curing for 4h, the stone can be transported or transferred. At the same time, after curing for 12h, the tensile shear strength reaches 8.6MPa, which meets the processing requirements of the stone. In particular, after curing for 24 hours, the tensile shear strength is further enhanced to 13.2MPa, and the hardness reaches 71D, which also meets the processing requirements of the stone. In addition, the two-component epoxy adhesive of the present invention can also meet the use requirements of stone, such as low viscosity (21mPa·s / 25°C), excellent permeability, good repair effect, low stone breakage rate, high gloss (118Gu), good yellowing resistance (5h), and will not affect the quality of the stone.

[0060] Example 2

[0061] A two-component epoxy adhesive for stone processing, comprising component A and component B;

[0062] Component A includes the following raw material components in terms of weight percentage:

[0063] And the sum of the weight percentages of each raw material is 100%;

[0064] Component B includes the following raw material components in terms of weight percentage:

[0065] Curing agent 44%,

[0066] Alicyclic amine modified curing agent 53%,

[0067] The accelerator is 3%, and the sum of the weight percentages of each raw material is 100%.

[0068] In this embodiment, the modified diluent is prepared from polypropylene glycol and epichlorohydrin, which includes the following steps: mixing polypropylene glycol and epichlorohydrin, and performing etherification, cyclization and purification under alkaline conditions to obtain the modified diluent.

[0069] In this embodiment, the molar ratio of polypropylene glycol to epichlorohydrin is 2: 1. The polypropylene glycol is polypropylene glycol 200 or polypropylene glycol 400.

[0070] In this embodiment, the epoxy equivalent of the modified diluent is 152 g / mol.

[0071] In this embodiment, the epoxy resin is a mixture of bisphenol A epoxy resin and bisphenol F epoxy resin, and the weight ratio of bisphenol A epoxy resin to bisphenol F epoxy resin is 73:27. The epoxy equivalent of the epoxy resin is 185 g / mol.

[0072] In this embodiment, the auxiliary agent is a modified product of acrylic acid and pentaerythritol, and the molar ratio of acrylic acid to pentaerythritol is 3:1.

[0073] In this embodiment, the coupling agent is KH560, or KH570, or a mixture thereof.

[0074] In this embodiment, the curing agent is polyetheramine D230, and may also be 1.3-BAC or triethylenetetramine.

[0075] In this embodiment, the accelerator is a mixture of benzyl alcohol and salicylic acid, wherein the weight ratio of benzyl alcohol to salicylic acid is 77:23.

[0076] In this embodiment, the alicyclic amine modified curing agent is prepared from an alicyclic amine curing agent and an epoxy resin mixed solution, comprising the following steps: adding the alicyclic amine curing agent into a reactor, adjusting the temperature to 32°C to 36°C, dripping the epoxy resin benzyl alcohol solution for 3h to 4h, and after the dripping is completed, adjusting the temperature to 38°C to 42°C and continuing the reaction for 2h to obtain the alicyclic amine modified curing agent, wherein the weight ratio of the alicyclic amine curing agent to the epoxy resin mixed solution is 73:27, the alicyclic amine curing agent includes IPDA and PACM, the weight ratio of IPDA to PACM is 37:63, and the epoxy resin mixed solution includes epoxy resin E-51 and benzyl alcohol, and the weight ratio of epoxy resin E-51 to benzyl alcohol is 7:13.

[0077] In this embodiment, the weight ratio of component A to component B is 3:1.

[0078] A method for preparing the two-component epoxy adhesive in the present embodiment comprises the following steps:

[0079] S1. Heat 78.0g of epoxy resin to 60℃~65℃, add 12.0g of modified diluent, 8.0g of auxiliary agent and 2.0g of coupling agent in sequence, stir for 80 minutes to obtain component A. Mix 44.0g of curing agent, 53.0g of alicyclic amine modified curing agent and 3.0g of accelerator, adjust the temperature to 25℃~35℃, stir for 80 minutes to obtain component B;

[0080] S2. Mix component A and component B to obtain a two-component epoxy adhesive, which can be used directly.

[0081] An application of the two-component epoxy adhesive in the present embodiment in stone processing is to apply the two-component epoxy adhesive to the surface of high-grade stone at 25°C.

[0082] After testing: the performance of the two-component epoxy adhesive in this embodiment is shown in Table 1. In addition, the two-component epoxy adhesive in this embodiment is applied to the surface of high-grade stone, cured at a temperature of 25°C, and its hardness and strength during the operation time are tested, and the results are shown in Table 1. The results show that after the two-component epoxy adhesive of the present invention is applied to the surface of the stone, the tensile shear strength reaches 4.8MPa after curing for 4h, that is, after curing for 4h, the stone can be transported or transferred. At the same time, after curing for 12h, the tensile shear strength reaches 9MPa, which meets the processing requirements of the stone. In particular, after curing for 24 hours, the tensile shear strength is further enhanced to 14.1MPa, and the hardness reaches 73D, which also meets the processing requirements of the stone. In addition, the two-component epoxy adhesive of the present invention can also meet the use requirements of stone, such as low viscosity (28mPa·s / 25°C), excellent permeability, good repair effect, low stone breakage rate, high gloss (119Gu), good yellowing resistance (5h), and will not affect the quality of the stone.

[0083] Example 3

[0084] A two-component epoxy adhesive for stone processing, comprising component A and component B;

[0085] Component A includes the following raw material components in terms of weight percentage:

[0086] And the sum of the weight percentages of each raw material is 100%;

[0087] Component B includes the following raw material components in terms of weight percentage:

[0088] Curing agent 40%,

[0089] Alicyclic amine modified curing agent 57%,

[0090] The accelerator is 3%, and the sum of the weight percentages of each raw material is 100%.

[0091] In this embodiment, the modified diluent is prepared from polypropylene glycol and epichlorohydrin, which includes the following steps: mixing polypropylene glycol and epichlorohydrin, and performing etherification, cyclization and purification under alkaline conditions to obtain the modified diluent.

[0092] In this embodiment, the molar ratio of polypropylene glycol to epichlorohydrin is 2: 1. The polypropylene glycol is polypropylene glycol 200 or polypropylene glycol 400.

[0093] In this embodiment, the epoxy equivalent of the modified diluent is 152 g / mol.

[0094] In this embodiment, the epoxy resin is a mixture of bisphenol A epoxy resin and bisphenol F epoxy resin, and the weight ratio of bisphenol A epoxy resin to bisphenol F epoxy resin is 73:27. The epoxy equivalent of the epoxy resin is 185 g / mol.

[0095] In this embodiment, the auxiliary agent is a modified product of acrylic acid and pentaerythritol, and the modified mol ratio is 3:1.

[0096] In this embodiment, the coupling agent is KH560, or KH570, or a mixture thereof.

[0097] In this embodiment, the curing agent is polyetheramine D230, and may also be 1.3-BAC or triethylenetetramine.

[0098] In this embodiment, the accelerator is a mixture of benzyl alcohol and salicylic acid, wherein the weight ratio of benzyl alcohol to salicylic acid is 77:23.

[0099] In this embodiment, the alicyclic amine modified curing agent is prepared from an alicyclic amine curing agent and an epoxy resin mixed solution, comprising the following steps: adding the alicyclic amine curing agent into a reactor, adjusting the temperature to 32°C to 36°C, dripping the epoxy resin benzyl alcohol solution for 3h to 4h, and after the dripping is completed, adjusting the temperature to 38°C to 42°C and continuing the reaction for 2h to obtain the alicyclic amine modified curing agent, wherein the weight ratio of the alicyclic amine curing agent to the epoxy resin mixed solution is 73:27, the alicyclic amine curing agent includes IPDA and PACM, the weight ratio of IPDA to PACM is 37:63, and the epoxy resin mixed solution includes epoxy resin E-51 and benzyl alcohol, and the weight ratio of epoxy resin E-51 to benzyl alcohol is 7:13.

[0100] In this embodiment, the weight ratio of component A to component B is 3:1.

[0101] A method for preparing the two-component epoxy adhesive in the present embodiment comprises the following steps:

[0102] S1. Heat 75.0g of epoxy resin to 60℃~65℃, add 13.0g of modified diluent, 9.0g of auxiliary agent and 3.0g of coupling agent in sequence, stir for 80 minutes to obtain component A. Mix 40.0g of curing agent, 57.0g of alicyclic amine modified curing agent and 3.0g of accelerator, adjust the temperature to 25℃~35℃, stir for 80 minutes to obtain component B;

[0103] S2. Mix component A and component B to obtain a two-component epoxy adhesive, which can be used directly.

[0104] An application of the two-component epoxy adhesive in the present embodiment in stone processing is to apply the two-component epoxy adhesive to the surface of high-grade stone at 25°C.

[0105] After testing: the performance of the two-component epoxy adhesive in this embodiment is shown in Table 1. In addition, the two-component epoxy adhesive in this embodiment is applied to the surface of high-grade stone, cured at a temperature of 25°C, and its hardness and strength during the operation time are tested, and the results are shown in Table 1. The results show that after the two-component epoxy adhesive of the present invention is applied to the surface of the stone, the tensile shear strength reaches 4.5MPa after curing for 4h, that is, after curing for 4h, the stone can be transported or transferred. At the same time, after curing for 12h, the tensile shear strength reaches 8.8MPa, which meets the processing requirements of the stone. In particular, after curing for 24 hours, the tensile shear strength is further enhanced to 13.8MPa, and the hardness reaches 73D, which also meets the processing requirements of the stone. In addition, the two-component epoxy adhesive of the present invention can also meet the use requirements of stone, such as low viscosity (27mPa·s / 25°C), excellent permeability, good repair effect, low stone breakage rate, high gloss (117Gu), good yellowing resistance (5h), and will not affect the quality of the stone.

[0106] Comparative Example 1

[0107] A two-component epoxy adhesive for stone processing, comprising component A and component B;

[0108] Component A includes the following raw material components in terms of weight percentage:

[0109] And the sum of the weight percentages of each raw material is 100%;

[0110] Component B includes the following raw material components in terms of weight percentage:

[0111] Curing agent 42%,

[0112] Alicyclic amine modified curing agent 55%,

[0113] The accelerator is 3%, and the sum of the weight percentages of each raw material is 100%.

[0114] In Comparative Example 1, except for the different amounts of the raw materials, other conditions are the same as those of Example 3.

[0115] After testing: the performance of the two-component epoxy adhesive in comparative example 1 is shown in Table 1. In addition, the two-component epoxy adhesive in comparative example 1 was applied to the surface of high-grade stone, cured at a temperature of 25°C, and its hardness and strength during the operation time were tested, and the results are shown in Table 1. The results show that after the two-component epoxy adhesive in comparative example 1 was applied to the surface of the stone, the tensile shear strength reached 0MPa (no strength) after curing for 4h, that is, after curing for 4h, the stone could not be transported or transferred. At the same time, after curing for 12h, the tensile shear strength reached 5.6MPa (the standard is ≥8.0MPa), which does not meet the processing requirements of the stone. In particular, after curing for 24 hours, its tensile shear strength was further enhanced to 7.6MPa (the standard is ≥8.0MPa), which still does not meet the processing requirements of the stone. In addition, the two-component epoxy adhesive in Comparative Example 1 has a very high viscosity (58 mPa·s / 25°C), poor permeability, low gloss (96 Gu), and poor yellowing resistance (4.5 h), which will reduce the quality of the stone and cannot meet the requirements for stone use.

[0116] Comparative Example 2

[0117] A two-component epoxy adhesive for stone processing, comprising component A and component B;

[0118] Component A includes the following raw material components in terms of weight percentage:

[0119] And the sum of the weight percentages of each raw material is 100%;

[0120] Component B includes the following raw material components in terms of weight percentage:

[0121] Curing agent 42%,

[0122] Alicyclic amine modified curing agent 55%,

[0123] The accelerator is 3%, and the sum of the weight percentages of each raw material is 100%.

[0124] In Comparative Example 2, except for the different amounts of the raw materials, other conditions are the same as those of Example 3.

[0125] After testing: the performance of the two-component epoxy adhesive in Comparative Example 2 is shown in Table 1. In addition, the two-component epoxy adhesive in Comparative Example 2 was applied to the surface of high-grade stone, cured at a temperature of 25°C, and its hardness and strength during the operation time were tested, and the results are shown in Table 1. The results show that after the two-component epoxy adhesive in Comparative Example 2 was applied to the surface of the stone, the tensile shear strength reached 0MPa (no strength) after curing for 4h, that is, after curing for 4h, the stone could not be transported or transferred. At the same time, after curing for 12h, the tensile shear strength reached 4.2MPa (the standard is ≥8.0MPa), which did not meet the processing requirements of the stone. In particular, after curing for 24 hours, its tensile shear strength was further enhanced to 7.4MPa (the standard is ≥8.0MPa), which still did not meet the processing requirements of the stone, and the hardness reached 80D, and the adhesive layer was too hard to be polished. In addition, the two-component epoxy adhesive in Comparative Example 2 has a very high viscosity (72 mPa·s / 25° C.), poor permeability, and poor yellowing resistance (3.0 h), which will reduce the quality of the stone and cannot meet the requirements for stone use.

[0126] Comparative Example 3

[0127] A two-component epoxy adhesive for stone processing, comprising component A and component B;

[0128] Component A includes the following raw material components in terms of weight percentage:

[0129] And the sum of the weight percentages of each raw material is 100%;

[0130] Component B includes the following raw material components in terms of weight percentage:

[0131] Curing agent 42%,

[0132] Alicyclic amine modified curing agent 55%,

[0133] The accelerator is 3%, and the sum of the weight percentages of each raw material is 100%.

[0134] In Comparative Example 3, except for the different amounts of the raw materials, other conditions are the same as those of Example 3.

[0135] After testing: the performance of the two-component epoxy adhesive in comparative example 3 is shown in Table 1. In addition, the two-component epoxy adhesive in comparative example 3 is applied to the surface of high-grade stone, cured at a temperature of 25°C, and its hardness and strength during the operation time are tested, and the results are shown in Table 1. The results show that after the two-component epoxy adhesive in comparative example 3 is applied to the surface of the stone, the tensile shear strength reaches 0MPa (no strength) after curing for 4h, that is, after curing for 4h, the stone cannot be transported or transferred. At the same time, after curing for 12h, the tensile shear strength reaches 4.0MPa, which does not meet the processing requirements of the stone. In particular, after curing for 24 hours, its tensile shear strength is further enhanced to 7.2MPa (the standard is ≥8.0MPa), which still does not meet the processing requirements of the stone. In addition, the two-component epoxy adhesive in comparative example 3 has a high viscosity (50mPa·s / 25°C), poor permeability, and poor yellowing resistance (3.1h), which will reduce the quality of the stone and cannot meet the requirements for the use of the stone.

[0136] Comparative Example 4

[0137] A two-component epoxy adhesive for stone processing, comprising component A and component B;

[0138] Component A includes the following raw material components in terms of weight percentage:

[0139] And the sum of the weight percentages of each raw material is 100%;

[0140] Component B includes the following raw material components in terms of weight percentage:

[0141] Curing agent 42%,

[0142] Alicyclic amine modified curing agent 55%,

[0143] The accelerator is 3%, and the sum of the weight percentages of each raw material is 100%.

[0144] In Comparative Example 4, except for the different amounts of the raw materials, other conditions were the same as those of Example 3.

[0145] After testing: the performance of the two-component epoxy adhesive in comparative example 4 is shown in Table 1. In addition, the two-component epoxy adhesive in comparative example 4 was applied to the surface of high-grade stone, cured at a temperature of 25°C, and its hardness and strength during the operation time were tested, and the results are shown in Table 1. The results show that after the two-component epoxy adhesive in comparative example 4 was applied to the surface of the stone, the tensile shear strength reached 0MPa (no strength) after curing for 4h, that is, after curing for 4h, the stone could not be transported or transferred. At the same time, after curing for 12h, the tensile shear strength reached 2.5MPa, and the stone still could not be transported or transferred. In particular, after curing for 24 hours, its tensile shear strength was further enhanced to 7.4MPa (the standard is ≥8.0MPa), which did not meet the processing requirements of the stone, and the hardness was 63D (the standard is ≥70D), and the adhesive layer was still soft and could not be polished. In addition, the two-component epoxy adhesive in Comparative Example 4 has poor yellowing resistance (2.5h), which will reduce the quality of the stone and cannot meet the requirements for stone use.

[0146] Comparative Example 5

[0147] A two-component epoxy adhesive for stone processing, comprising component A and component B;

[0148] Component A includes the following raw material components in terms of weight percentage:

[0149] And the sum of the weight percentages of each raw material is 100%;

[0150] Component B includes the following raw material components in terms of weight percentage:

[0151] Curing agent 42%,

[0152] Alicyclic amine modified curing agent 55%,

[0153] The accelerator is 3%, and the sum of the weight percentages of each raw material is 100%.

[0154] In Comparative Example 5, except for the different amounts of the raw materials, other conditions are the same as those of Example 3.

[0155] After testing: the performance of the two-component epoxy adhesive in comparative example 5 is shown in Table 1. In addition, the two-component epoxy adhesive in comparative example 5 was applied to the surface of high-grade stone, cured at a temperature of 25°C, and its hardness and strength during the operation time were tested, and the results are shown in Table 1. The results show that after the two-component epoxy adhesive in comparative example 5 was applied to the surface of the stone, the tensile shear strength reached 0MPa (no strength) after curing for 4h, that is, after curing for 4h, the stone could not be transported or transferred. At the same time, after curing for 12h, the tensile shear strength reached 2.6MPa, and the stone still could not be transported or transferred. In particular, after curing for 24 hours, its tensile shear strength was further enhanced to 7.1MPa (the standard is ≥8.0MPa), which did not meet the processing requirements of the stone, and the hardness was 61D (the standard is ≥70D), and the adhesive layer was still soft and could not be polished. In addition, the two-component epoxy adhesive in Comparative Example 5 has poor yellowing resistance (2.5h), which will reduce the quality of the stone and cannot meet the requirements for stone use.

[0156] Table 1 Performance comparison of different two-component epoxy adhesives

[0157]

[0158]

[0159] The test methods for each property in Table 1 are conventional methods and will not be described in detail here.

[0160] From the above results, it can be seen that compared with conventional two-component epoxy adhesives, the two-component epoxy adhesive of the present invention exhibits more excellent performance, such as higher strength, lower viscosity, higher gloss, and a shorter time required to reach early strength. It is a new type of epoxy resin surface adhesive with excellent performance and can be widely used in stone processing. It can be widely used in the processing and production of stone, has high use value, and good application prospects.

[0161] The above embodiments are only preferred implementations of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A two-component epoxy adhesive for stone processing, characterized in that: It includes component A and component B; The component A comprises the following raw material components in terms of weight percentage: The B component comprises the following raw material components in terms of weight percentage: Curing agent 37%~44%, Alicyclic amine modified curing agent 53%~61%, The accelerator is 2% to 3%, and the sum of the weight percentages of each raw material is 100%; The modified diluent is prepared from polypropylene glycol and epichlorohydrin; the auxiliary agent is a modified product of acrylic acid and pentaerythritol.

2. The two-component epoxy adhesive according to claim 1, characterized in that: The preparation method of the modified diluent comprises the following steps: mixing polypropylene glycol and epichlorohydrin, and performing etherification, cyclization and purification under alkaline conditions to obtain the modified diluent; the molar ratio of the polypropylene glycol to epichlorohydrin is 2:1; and the polypropylene glycol is polypropylene glycol 200 and / or polypropylene glycol 400.

3. The two-component epoxy adhesive according to claim 2, characterized in that: The epoxy equivalent of the modified diluent is 147.5 g / mol to 167.5 g / mol.

4. The two-component epoxy adhesive according to any one of claims 1 to 3, characterized in that: The epoxy resin is a mixture of bisphenol A epoxy resin and bisphenol F epoxy resin; the weight ratio of the bisphenol A epoxy resin to the bisphenol F epoxy resin is 14-15:5-6; the epoxy equivalent of the epoxy resin is 185g / mol-188g / mol.

5. The two-component epoxy adhesive according to any one of claims 1 to 3, characterized in that: The molar ratio of acrylic acid to pentaerythritol in the auxiliary agent is 3:1; and the coupling agent is at least one of KH560 and KH570.

6. The two-component epoxy adhesive according to any one of claims 1 to 3, characterized in that: The curing agent is at least one of triethylenetetramine, 1.3-BAC, and polyetheramine D230; The accelerator is a mixture of benzyl alcohol and salicylic acid; the weight ratio of benzyl alcohol to salicylic acid is 72-81:19-28; The alicyclic amine modified curing agent is prepared from a mixed solution of alicyclic amine curing agent and epoxy resin, and comprises the following steps: adding the alicyclic amine curing agent into a reactor, adjusting the temperature to 32°C-36°C, dripping the epoxy resin benzyl alcohol solution for 3h-4h, and after the dripping is completed, adjusting the temperature to 38°C-42°C and continuing the reaction for 2h to obtain the alicyclic amine modified curing agent; the weight ratio of the alicyclic amine curing agent to the epoxy resin mixed solution is 13-15:5-7; the alicyclic amine curing agent comprises IPDA and PACM; the weight ratio of IPDA to PACM is 7-8:12-13; the epoxy resin mixed solution comprises epoxy resin E-51 and benzyl alcohol; the weight ratio of the epoxy resin E-51 to benzyl alcohol is 3-4:6-7.

7. The two-component epoxy adhesive according to any one of claims 1 to 3, characterized in that: The weight ratio of the component A to the component B is 2.90-3.10:

1.

8. A method for preparing a two-component epoxy adhesive as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Heat the epoxy resin to 60°C to 65°C, add a modified diluent, an auxiliary agent and a coupling agent in sequence, stir, and obtain component A; mix the curing agent, the alicyclic amine modified curing agent and the accelerator, adjust the temperature to 25°C to 35°C, stir, and obtain component B; S2. Mix component A and component B to obtain a two-component epoxy adhesive.

9. The preparation method according to claim 8, characterized in that: During the preparation of component A, the stirring time is 75 min to 90 min; During the preparation of the component B, the stirring time is 75 min to 90 min.

10. Use of the two-component epoxy adhesive according to any one of claims 1 to 7 or the two-component epoxy adhesive prepared by the preparation method according to claim 8 or 9 in stone processing.